INVESTIGATION OF FACTORS ASSOCIATED CHRONIC MECHANIC NECK PAIN - Mustafa Yıldız,; Hakan Tuna,; Burcu Tokuç,; Siranuş Kokino, (Archives of Rheumatology, 2005)
Although there are many investigations about chronic low back pain associated factors, there are few investigations about chronic neck pain associated factors in our country. Therefore, this study was aimed to the chronic neck pain data in our country was gathered through this investigation. The correlation of the characteristic values, psychosocial status, working factors, exercise habit, the current intensity of pain, duration of pain, and localization of maximum pain, factors that relieve or exacerbate pain were investigated in 100 patients with chronic neck pain. Physical load was highest (%49) in pain exacerbate factors. On the other hand drugs were highest (%66) in pain relieve factors. The exacerbate and/or initial chronic neck pain factors were detected to the body position included bending (%34), arising (%29), walking (%29) and the head motion included left bending (%41), right bending (%40), back bending(%40). In conclusion, further studies results about chronic mechanic neck pain associated factors would provide to contents in patient education programmes.